Synthesis of 1,4-cyclohexanedimethanol by hydrogenation of dimethyl terephthalate and its application as a substrate in syntheses of polyesters - Lewandowski, G.; Wróblewska, A.; Milchert, E. (Polimery, 2022)
A review concerning the preparation of alicyclic diol 1,4-cyclohexanedimethanol (CHDM), being the substrate for the polyesters' syntheses, is presented. CHDM synthesis consists of two-stage hydrogenation of dimethyl terephthalate [equation (1) and (2)]. Dimethyl 1,4-cyclohexanedicarboxylate (CHDKM) is an intermediate product in the process. General conditions of both stages of the process were given (catalyst, temperature, pressure) and technological solutions (Fig. 1) were discussed in detail. Polyesters and copolyesters produced with use of CHDM were characterized and their useful advantages (high melting point, significant crystallinity, good thermal stability and mechanical strength) were stressed. Most important directions of applications have been presented.